Review of the monograph Russia's War Against Ukraine: Paradoxes Through the Looking Glass (Essayistic Reflections) - BILOVUS, Lesya (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
Review of the monograph Russia's War Against Ukraine: Paradoxes Through the Looking Glass (Essayistic Reflections)